Nociception Coma Scale with personalized painful stimulation versus standard stimulus in non-communicative patients with disorders of consciousness. Issue 10 (25th November 2020) - Formisano, R.; Contrada, M.; Aloisi, M.; Ferri, G.; Schiattone, S.; Iosa, M.; Buzzi, M.G.
ABSTRACT: Introduction: Persons with disorders of consciousness (DoC) may perceive pain without being able to communicate their discomfort. Nociception Coma Scale (NCS) and its revised form (NCS-R) have been proposed to assess nociception in coma survivors with DoC. Objective: Aim of the present study was to compare, in non-communicative patients with DoC, NCS-R scores obtained with the standard pressure on fingernail bed (standard stimulus, SS) versus other personalized painful stimuli (PS), to verify possible correlations between NCS-R and Coma Recovery Scale-Revised (CRS-R). Materials and Methods: Twenty-one patients with DoC were included in the study. Responsiveness and pain perception were assessed by CRS-R and NCS-R with standard stimulus (NCS-R-SS) and personalized stimulation (NCS-R-PS). Statistical analysis was performed with the nonparametric Wilcoxon test for comparison of both total NCS-R-SS and NCS-R-PS scores. Results: NCS-R at admission showed that 9 of 21 patients (42.8%) had higher scores in response to personalized stimulus compared to standard stimulus. Significant correlation with CRS-R were found for both NCS-R-SS ( R  = 0.701, p  = .008) and NCS-R-PS ( R  = 0.564, p  = .045). Discussion: The preliminary results obtained in the present study suggest that NCS-R-PS may disclose pain perception in a larger number of non-communicative patients with DoC, compared to NCS-R-SS.